Not Like Everybody Else. Essays in Honor of Kees Mandemakers - Jan Kok; Hilde Bras; Richard L. Zijdeman (Historical Life Course Studies)
This collection of essays pays tribute to Kees Mandemaker's great contribution to the data infrastructure of social science history, in the Netherlands and elsewhere. Several essays discuss (the future of) historical databases. Yet other provide examples of research on topics covering important life course transitions. All demonstrate the scale, scope and variation of research based on well-constructed databases.